Exploring human papillomavirus vaccine hesitancy among college students and the potential of virtual reality technology to increase vaccine acceptance: a mixed-methods study - Yoon, Sangchul; Kim, Heeyeon; An, Juhyeong; Jin, Seok Won (Frontiers in Public Health, 2024)
Background Human papillomavirus (HPV) can cause cancers in men and women. Despite the availability of an effective vaccine, HPV vaccination coverage remains suboptimal among college students. Literature showed that hesitancy for HPV vaccination is a leading barrier to the uptake in this group. However, prior interventions have shown limitations in reducing HPV vaccine hesitancy in college students. Thus, this study examined a conventional educational approach using a vaccine information statement (VIS), and subsequently explored college students’ HPV vaccine hesitancy and the potential of virtual reality (VR) technology to overcoming the limitations of interventional efforts. Methods We employed a mixed-methods design along with convenience sampling, constituting a one-way pre- and post-intervention (HPV VIS) survey (Study A) and individual interviews (Study B). All data collections occurred with 44 college students at an urban public university at the mid-south region of the U.S. between October 2022 and April 2023. Study A assessed changes in HPV vaccination outcomes including knowledge, beliefs/attitudes, vaccine hesitancy, and intentions. Study B measured college students’ primary reasons for HPV vaccine hesitancy and preferred strategies for the vaccination promotion including VR-based education. We conducted paired t-test and Wilcoxon signed ranks test for quantitative data and framework analysis for qualitative data. Results Participants reported significant improvements in knowledge [t(43) = 6.68, p < 0.001] regarding HPV vaccination between before and after reading the HPV VIS. No change was observed in beliefs/attitudes, vaccine hesitancy, and intentions. The framework analysis revealed college students’ reasons for HPV vaccine hesitancy, needed information, and preferred strategies along with the potential of VR technology for future HPV vaccination education. Conclusion The findings provided essential information on designing HPV vaccination information focused on vaccine hesitancy among college students. Future research should consider these findings in developing interventions including VR to increasing HPV vaccine acceptance among college students.